Twin foetus papyraceous in triplet pregnancy - Gulati, Gunjan; Das, Banashree; ., Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The occurrence of twin papyraceous foetuses in triplet pregnancy is rare. A papyraceous foetus is found almost exclusively in multiple pregnancy. Papyraceous foetus is most frequent in foetuses dying between the third and sixth months of development. No convincing information has been obtained about the cause of early death of one or more foetuses and continued development of one or more others. There are rarely any symptoms or signs that suggest occurrence of foetus papyraceous, and a definite diagnosis can be made only at the time of delivery. Even then it may be missed by careless examination. We report here a case of a 25 year female with triplet pregnancy who delivered a healthy baby at term with two foetus papyracei.